Spinal cord involvement by atrophy and associations with disability are different between multiple sclerosis and neuromyelitis optica spectrum disorder. (2nd August 2019) - Nakamura, Y.; Liu, Z.; Fukumoto, S.; Shinoda, K.; Sakoda, A.; Matsushita, T.; Hayashida, S.; Isobe, N.; Watanabe, M.; Hiwatashi, A.; Yamasaki, R.; Kira, J. ‐i.
Abstract : Background and purpose: The cervical and thoracic cross‐sectional spinal cord area (CS‐SCA) in multiple sclerosis (MS) correlates with disability, whilst such a correlation remains to be established in neuromyelitis optica spectrum disorder (NMOSD). Our aim was to clarify differences between MS and NMOSD in spinal cord segments where CS‐SCA is associated with disability. Methods: The CS‐SCA at C2/C3, C3/C4, T8/T9 and T9/T10 vertebral disc levels was measured in 140 MS patients (111 with relapsing–remitting MS and 29 with progressive MS) and 42 NMOSD patients with anti‐aquaporin‐4 immunoglobulin G. Disability was evaluated by Expanded Disability Status Scale (EDSS) scores. Multivariate associations between CS‐SCA and disability were assessed by stepwise forward multiple linear regression. Results: Thoracic CS‐SCA was significantly smaller in NMOSD patients than in MS patients even after adjusting for age, sex and disease duration ( P  =   0.002 at T8/T9), whilst there was no difference in cervical CS‐SCA between the two diseases. Cervical and thoracic CS‐SCA had a negative correlation with EDSS scores in MS patients ( P  <   0.0001 at C3/C4 and P  =   0.0002 at T8/T9) whereas only thoracic CS‐SCA correlated with EDSS scores in NMOSD patients ( P  =   0.0006 at T8/T9). By multiple regression analyses, predictive factors for disability in MS were smaller cervical CS‐SCA, progressive course, older age and a higher number of relapses, whilst those in NMOSD were smaller thoracic CS‐SCA and older age. Conclusions: Thoracic CS‐SCA is a useful predictive marker for disability in patients with NMOSD whilst cervical CS‐SCA is associated with disability in patients with MS.